The fossil pulmonate snails of Sandelzhausen (Early/Middle Miocene, Germany): Succineidae, Testacelloidea and Helicoidea - Salvador, Rodrigo Brincalepe (Zootaxa, 2013)
Sandelzhausen is an Early/Middle Miocene (Mammal Neogene zone MN5) fossil site near Mainburg, S Germany, and despite its small size it harbors a rich fossil record. Hundreds of fossil continental mollusks, almost exclusively pulmonates snails, were recovered during the excavations, but never received due attention by researchers. Here, the second part of a formal taxonomical treatment of the fossil pulmonates from Sandelzhausen is presented, dealing with the superfamilies Succineoidea, Testacelloidea and Helicoidea, and including the description of a new hygromiid species. The following species were found in the material: Succinea minima (Succineidae); Palaeoglandina sp. (Spiraxidae); Testacella zellii (Testacellidae); Klikia cf. coarctata (Elonidae); Cepaea cf. eversa, Cepaea cf. sylvestrina and Tropidomphalus cf. incrassatus (Helicidae); ?Helicodonta sp. and Helicodontidae indet. (Helicodontidae); Leucochroopsis kleinii and Urticicola perchtae sp. nov. (Hygromiidae).